Psychiatry and postmodern theory: Postpsychiatry. Review - Cruz M., Carlos (Revista de Psiquiatría Clínica, 2021)
Psychiatry is by excellence a modernist project and a paradigmatic application of the aspirations of the Enlightenment. Postmodern theory provides a liberation effect on modernist practices. and the “scientific method” works in a modernist discourse as a meta-narrative. Postmodern psychiatry would appeal to the wisdom of the community of practice. Post-psychiatry is a variant of critical psychiatry. From a positivist epistemology, biopsychiatry uses the methods of the natural sciences for the explanation of human experience. In this postpsychiatric framework in which the assumptions of the users are the starting point, the therapeutic relationship is horizontal and the professionals are at their service. The imperfections of the medical mind can not be underestimated. Neither can the negative consequences of their claim be the only legitimate psychiatric paradigm. However, psychiatry can not do without the medical mind.